RELIGIOUS IDEOLOGY OF THE TRADITION OF MAKOTEK IN THE ERA OF GLOBALIZATION - Pradana, Gede Yoga Kharisma; Suarka, I Nyoman; Wirawan, A.A. Bagus; Dhana, I Nyoman (E-Journal of Cultural Studies, 2016)
Makotek is a cultural tradition which is performed as a ritual to ward off misfortune by the people living at Munggu Village, Badung Regency. It is performed once in six months, namely, every Kuningan Feast Day.  It has been inherited from generation to generation as an oral tradition. In the era of globalization, many parties and cultural components are involved in its performance.  It is still performed until now. However, the people living at Munggu Village do not close themselves to modernity. The data were collected through observation, interview, library research and documentary techniques. The informants were determined using the purposive and snowball technique. All the data were analyzed in order to draw conclusions. The result of the study shows that the religious ideology which has inspired the people living at Munggu Traditional Village to perform the tradition of Makotek . Ideologically, they believe that by performing the tradition of Makotek , they can protect their resources and the human unity in the middle of the social dynamics in the era of globalization. It is performed in stages, in accordance with the tradition they have adhered to since a long time ago. The performance of the tradition of Makotek at Munggu Village has been able to strengthen their belief in the existence of Ida Sang Hyang Widhi , Almighty God. In addition, such a religious practice is the supernatural source of happiness and health as it is believed to be able ward off misfortune.
Keywords: religious ideology, performance of tradition of makotek, globalization era.